2016
DOI: 10.1016/j.aott.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Weakening iliopsoas muscle in healthy adults may induce stiff knee pattern

Abstract: ObjectiveThe goal of the present study was to investigate the relationship between iliopsoas muscle group weakness and related hip joint velocity reduction and stiff-knee gait (SKG) during walking in healthy individuals.MethodsA load of 5% of each individual's body weight was placed on non-dominant thigh of 15 neurologically intact, able-bodied participants (average age: 22.4 ± 0.81 years). For 33 min (135 s × 13 repetitions × 5 s rest), a passive stretch (PS) was applied with the load in place until hip flexo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…The deep multifidus and the superficial erector spine muscle play an important role in the stability of the trunk ( 36 ). If they degenerate, it will lead to the imbalance of the spine in the sagittal position ( 37 , 38 ), leading to the forward shift of the whole center of gravity and the compensatory increase of the oblique angle of the pelvis ( 39 ). The asymmetric distribution of multifidus is a risk factor for degenerative spondylolisthesis ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The deep multifidus and the superficial erector spine muscle play an important role in the stability of the trunk ( 36 ). If they degenerate, it will lead to the imbalance of the spine in the sagittal position ( 37 , 38 ), leading to the forward shift of the whole center of gravity and the compensatory increase of the oblique angle of the pelvis ( 39 ). The asymmetric distribution of multifidus is a risk factor for degenerative spondylolisthesis ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may result from a decrease in the ankle moment generated by the plantar flexor muscles [ 55 ] or in the peak of vertical acceleration of the lateral malleolus [ 8 ]. Finally, a third possible origin to SKG is the weakness of the hip flexor muscles [ 14 , 56 ]. In our results, the decrease in KFV was confirmed, as well as a decrease in mean ankle plantarflexion velocity in the preswing phase (MAVP).…”
Section: Discussionmentioning
confidence: 99%
“…Factors that could contribute to the large variability include parameters that cannot be influenced such as sex or body height and parameters that can be modified such as body mass or parameters of neuromuscular performance (e.g., muscle strength or muscle coordination). For instance, Akalan et al ( 2016 ) have shown that iliopsoas muscle group weakness resulted in related hip joint velocity reduction and stiff-knee gait during walking in healthy persons. However, the paradigm of a unique “foot acceleration print” similar to the previously proposed gait print (Broscheid et al, 2018 ) warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%